THE GLOBAL AGRICULTURAL SYSTEM AND CLIMATE CHANGE: CHALLENGES AND OPPORTUNITIES FOR THE RUSSIAN FEDERATION - R. Valentini (Финансы: теория и практика, 2017)
The article examines the dependence of the development of the global agricultural system against climate change of the planet. It is argued that agricultural production in the period beyond 2015 is playing an increasingly prominent role, and it will increase in future. The current vulnerability of climate system largely depends on a delicate balance between greenhouse gas emissions caused by human activities, a policy aimed at mitigating these harmful effects and the natural dynamics of the functioning of terrestrial and ocean systems. This, in turn, depends on the number of sources of greenhouse gases that affect climate. Unprecedented climate change seriously threatens agricultural production and food security. It is therefore essential the further development of new areas of science, including a reliable methodology for monitoring greenhouse gases, advanced modeling tools, collection and aggregation of big data. Despite the good preconditions for the development of the food sector, the risk of impacts of climate change on natural ecosystems remains high, even under favorable temperature conditions. Thus, solutions must be found in the change of our paradigms.We must change the attitude towards agriculture as a separate component of the food system. Agriculture should be an important element in mitigating the effects of climate change and adaptive strategies. The author argues that Russia is a promising candidate among the boreal regions. Russia is able to take advantage of the situation and to turn from an importer of agricultural products into solid world exporter of food. The article presents several factors that can become the basis for a new agricultural and food strategy of Russia. But to fully take advantage of such capabilities it is required significant transformation. Taking into account some changes in the agricultural sector, the author provides recommendations that could enhance the role of the Russian Federation on the agrofood world markets.